2019
DOI: 10.1029/2018jb017252
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluid Chemistry on the Interfacial Composition, Adhesion, and Frictional Response of Calcite Single Crystals—Implications for Injection‐Induced Seismicity

Abstract: While it has been shown that the mechanical properties and the reactivity of carbonate‐bearing rocks may be influenced by the chemical composition of the fluids, little is known about how the fluid composition affects their frictional response. Here, we have used atomic force microscopy to investigate the frictional characteristics of single calcite crystals in calcium carbonate saturated solutions and in two brines, NaCl and CaCl2, at a wide range of geologically relevant concentrations. Surface forces were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 125 publications
1
3
0
Order By: Relevance
“…6 A ). Although in our previous studies on smooth calcite crystals ( 11 , 12 ), we did not notice this linear relation, we have confirmed that it describes those reported results as well.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…6 A ). Although in our previous studies on smooth calcite crystals ( 11 , 12 ), we did not notice this linear relation, we have confirmed that it describes those reported results as well.…”
Section: Resultssupporting
confidence: 86%
“…A few atomic force microscopy (AFM) studies ( 14 17 ) have reported the stress-induced dissolution of minerals also while sliding. Our nanoscale studies with an AFM tip sliding on atomically smooth calcite crystals ( 11 , 12 ) showed a remarkable decrease of the kinetic friction coefficient and a prominent deviation from at high normal stresses. Experiments with a surface forces apparatus (SFA) revealed that the decrease in friction happens concurrently with the pressure-induced dissolution of calcite ( 13 ), a lubrication mechanism that we called “pressure solution–facilitated slip” ( 11 ).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In recent years, the complex processes occurring at calcite surfaces in contact with water have also been investigated by direct force measurements using techniques such as AFM 85,[103][104][105][106][107] and the surface forces apparatus (SFA). 85,108,109 The difference between these measurements and those reported previously is that the focus has shifted to events taking place between two calcite surfaces under compression and in close contact.…”
Section: Calcite Surfaces Under Confinementmentioning
confidence: 99%